Analisis Gaya Kepemimpinan Direktur Operasional PT Swakarya Pagaran Amerta dalam Perspektif Psikologi Kepemimpinan - Widya Maharani; Ana Yuliani; Sherly Yulitri; Azizah Meihana; Nayya Desrial Marsanda; Alifurizky Alifurizky; Suci Rahma Nio (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the leadership style implemented by the leader of PT Swakarya Pagaran Amerta from the perspective of leadership psychology. The research employed a qualitative method with a case study approach through direct interviews with the Operational Director of PT Swakarya Pagaran Amerta. The collected data were analyzed based on leadership theories, particularly democratic, transactional, and transformational leadership. The findings indicate that the company's leader applies a democratic leadership style characterized by open communication, employee involvement in decision-making processes, and appreciation of team members' opinions. In addition, transactional leadership practices are evident through the implementation of reward and punishment systems based on employee performance. The leader also demonstrates transformational leadership characteristics by providing motivation, guidance, and support for employee development. The combination of these leadership styles contributes to a positive work environment, enhances employee motivation, and supports the achievement of organizational goals effectively. Therefore, the leadership approach implemented not only focuses on organizational performance but also emphasizes human resource development and employee well-being.